2018
DOI: 10.24233/biov.4.2.2018.106
|View full text |Cite
|
Sign up to set email alerts
|

DIVERSITY OF EPIPHYTIC FERN ON THE OIL PALM PLANTS (Elaeis Guineensis Jacq.) IN CAMPUS OF SRIWIJAYA UNIVERSITY INDRALAYA

Abstract: The Campus of Sriwijaya University in Indralaya , has a high diversity of flora including fern, especially the epiphytic ferns, whose existence is so widely found in oil palm plants. This epiphytic study has been conducted from July to November 2017, with the aim of identifying the diversity of species of epiphytic ferns in oil palm plants on the campus of UNSRI Indralaya. The research method used is exploration method with direct collection technique from the field and then made herbarium. In this study found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Oloyede et al (2014) stated that N. biserrata was host-specific as most of the plants were found on the E. guineensis. However, this data proved that N. biserrata is not host-specific as this species can grow and make a thicked on many species of palm trees, although this species is a common epiphytic fern growing on oil palm plantation (E. guineensis) (Sofiyanti 2013;Adeleye et al 2017;Harmida et al 2018).…”
Section: Host Preferences Of Epiphytic Fern Species On Palm Treesmentioning
confidence: 86%
See 2 more Smart Citations
“…Oloyede et al (2014) stated that N. biserrata was host-specific as most of the plants were found on the E. guineensis. However, this data proved that N. biserrata is not host-specific as this species can grow and make a thicked on many species of palm trees, although this species is a common epiphytic fern growing on oil palm plantation (E. guineensis) (Sofiyanti 2013;Adeleye et al 2017;Harmida et al 2018).…”
Section: Host Preferences Of Epiphytic Fern Species On Palm Treesmentioning
confidence: 86%
“…There are a few of works on the documentation of ferns epiphytic flora growing on palm trees, see Sofiyanti (2013), Harmida et al (2018), Adeleye et al (2017), Prastyo et al (2015), Zotz and Volrath (2003), and Sato et al (1996). Most of these studies were focused on the diversity of epiphytic ferns on oil palm (Elaeis guineensis Jacq.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species include pteridophytes and nonpteridophytes. According to previous research by Harmida et al (2018) and Sofiyanti et al (2013), the most dominant pteridophytes species identified are Goniophlebium verrucosum and Nephrolepis bisserata. These species can grow well on the soil surface, indicating they are not true epiphytes.…”
Section: Epiphytes Abundancementioning
confidence: 82%
“…The 39 species found in the 120,000 square meters is relatively high compared with the 20 species recorded on the university campus of Indralaya (in Sumatra, Indonesia; the species comprising 16 terrestrial, 3 epiphytic and 1 aquatic fern); 17 and with the 27 epiphytic fern species noted in an oil palm plantation near the university. 18 The species diversity in our study site included eighteen genera represented by a single species. A few of the representatives of these genera are common species, but others are rare and occur with low frequencies, such as Ophioglossum, Psilotum and the Platicerium.…”
Section: Comparisonmentioning
confidence: 99%